2010
DOI: 10.1177/0145445510361331
|View full text |Cite
|
Sign up to set email alerts
|

Endurance of Multiplication Fact Fluency for Students With Attention Deficit Hyperactivity Disorder

Abstract: This study examines the relationship between a critical learning outcome of behavioral fluency and endurance, by comparing the effects of two practice procedures on multiplication facts two through nine. The first procedure, called whole time practice trial, consisted of an uninterrupted 1 minute practice time. The second procedure, endurance building practice trials, had three 20 second practice trials. A total of 3 students with attention deficit hyperactivity disorder participated. Results indicated that mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 10 publications
0
19
1
1
Order By: Relevance
“…Research investigating critical outcomes to date focuses primarily on application and retention with fewer examinations of endurance reported in the literature (Brady & Kubina, 2010). To date, no empirical investigations of this outcome have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research investigating critical outcomes to date focuses primarily on application and retention with fewer examinations of endurance reported in the literature (Brady & Kubina, 2010). To date, no empirical investigations of this outcome have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…A number of research studies to date have demonstrated the attainment of fluent performances as a result of frequency-building with mathematics skills (Hartnedy et al, 2005;Poncy, et al, 2010). Further, the attainment of fluent performances with component mathematics skills has been associated with improvements in endurance (Brady & Kubina, 2010;McDowell & Keenan, 2001) and application (Bucklin et al, 2000;Cavallini & Perini, 2009;Chiesa & Roberston, 2000;Kubina et al, 2004) as well as overall mathematical ability (Carr & Alexeev, 2011;Carr et al, 2008 …”
Section: Purpose Of the Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The potential effects of fluency instruction include (a) greater retention of skills taught (Binder 1996;Ivarie 1986), (b) better application or generalization of learned skills to new stimuli or situations (Binder and Bloom 1989;Johnson and Layng 1992), (c) higher rates of responding over a prolonged period of time (i.e., endurance) without the need for extrinsic reinforcement (Binder 1996;Binder et al 1990;Brady and Kubina 2010;McDowell and Keenan 2001), (d) higher rates of accurate responding in the presence of distractions (i.e., stability) or longer periods of attention (Binder 1996;Bloom 1986), and (e) faster learning of more complex skills involving combinations of ''fluent'' component skills (Haughton and Kovacs, as cited in Binder 1996;Van Houten 1980).…”
Section: Fluency Trainingmentioning
confidence: 99%